The Enduring Effects of Conditioned Flavor Cues, Associated with Alcohol-Drinking During Adolescence, on Cue-Induced Alcohol-Drinking and –Seeking in Adulthood - Taylor, Mckenzie (Digital Commons @ East Tennessee State University, 2019)
Introduction Alcoholism represents a chronic recurring disorder that affects 15 million people nationwide, 4% of which fall within the adolescent age range (12-17). Clinical data indicate that adolescents who binge drink greatly increase their chances of suffering from several dangerous health outcomes (i.e., suicide, risky sexual behavior, car wreck, etc.) as well as the likelihood they will develop an alcohol-use disorder later in life. Moreover, research indicates that cues (i.e. flavors) paired with alcohol drinking produce significant cue-induced alcohol craving, contributing to relapse in adolescence and adult populations. Therefore, the current study sought to model the effect of adolescent exposure to flavor cues, paired with alcohol, on subsequent cue-induced alcohol-seeking in adulthood. Methods Alcohol naïve alcohol-preferring (P) rats were randomly assigned to a paired or unpaired group. During the adolescent period, all animals had 24-hour access to 3 bottles; (paired group: 0.1% blueberry flavor extract (BB) + 15% v/v alcohol, and two water; unpaired group: 0.1% BB, 15% v/v alcohol, and water). The animal’s body and bottle weights were recorded daily. In the first two weeks of adulthood, all rats experienced daily 60-minute self-administration sessions to measure fluid intake. Paired animals could consume 0.1% BB + 15% alcohol or water and unpaired animals could consume 0.1% BB or 15% alcohol. The following two weeks all rats were kept in their home cage with access to only water. Following this 2 week period of imposed abstinence, rats were returned to the chambers and consumption of 0.1% BB or water was measured to examine cue-induced alcohol-seeking. Results Data indicate adolescent exposure to BB + alcohol did not promote faster acquisition of self-administration. Additionally, during adolescence and adulthood, both groups consumed similar levels of alcohol. When tested for cue-induced alcohol-seeking, paired rats exhibited significant resistance to extinction of sipping on the BB sipper (no alcohol). Conclusions Overall, data suggest that cues paired with alcohol during adolescence and early adulthood may contribute to prolonged alcohol-seeking behavior thus increasing risk of relapse following subsequent cue exposure.